Parental duties and untreatable genetic conditions - Clarkeburn, Henriikka (Journal of medical ethics, 2000)
This paper considers parental duties of beneficence and non-maleficence to use prenatal genetic testing for non-treatable conditions. It is proposed that this can be a duty only if the testing is essential to protect the interests of the child ie only if there is a risk of the child being born to a life worse than non-existence. It is argued here that non-existence can be rationally preferred to a severely impaired life. Uncontrollable pain and a lack of any opportunity to develop a continuous self are considered to be sufficient criteria for such preference. When parents are at risk of having a child whose life would be worse than non-existence, the parents have a duty to use prenatal testing and a duty to terminate an affected pregnancy. Further, such duty does not apply to any conditions where the resulting life can be considered better than non-existence.